Lifestyle Issues: What Do I Tell My Patients? Smoking and Diet. (1st November 1990) - Benoni, C
Abstract : During the past decade, smoking has been recognized as a risk factor in inflammatory bowel disease (IBD). Smoking is associated with Crohn's disease, and nonsmoking with ulcerative colitis. The biological rationale behind these findings is not known. Because of the negative effects of smoking, advice to patients with IBD cannot differ from advice given to any patient. In families with IBD, young healthy members should be advised never to start smoking. In Crohn's disease, a fat-reduced diet will be necessary when bile salt metabolism is disturbed. Prospective trials with unrefined carbohydrate fibre-rich diets or low-residue diets versus normal diets show no difference in the clinical course of Crohn's disease. Thus the patient should have a well balanced diet with unrestricted fibre intake, supplemented in case of malabsorption with vitamins and minerals. Diet counselling itself has proved beneficial, probably because of optimization of nutritional status. In ulcerative colitis, patients may be lactose intolerant without lactase deficiency. Low dietary fibre intake doses does not seem to be of importance. The ulcerative colitis patient should be advised to eat a normal to high fibre diet. Recent studies have suggested a possible beneficial effect of dietary supplementation with fish oil.